Case report: Hereditary sensory autonomic neuropathy presenting as bifid deformity to the tongue - O’Hagan-Wong, Kelsey; Smith, Dana; Gonorazky, Hernan; Casas, Michael (Frontiers in Dental Medicine, 2023)
Hereditary sensory autonomic neuropathy (HSAN) is a group of rare genetic disorders in which affected patients have a diminished capacity to feel pain. Patients with HSAN may present with a wide range of factitial injuries, where injury to the oral cavity may be an early presenting sign. While existing literature on HSAN is scant, many reports highlight the long-term outcomes that may include enucleation of eyes, amputation of fingers and limbs, and disfigurement of the tongue. This case describes a five-month-old female with repetitive injury to the tongue causing it to heal with a bifid deformity. The patient was later diagnosed with HSAN type 4. This case highlights the importance of recognition of extensive oral trauma as one of the early signs of HSAN that should provoke a timely referral for neurological assessment.